Development of Resilience and Analytical Competencies of Personnel of the Security and Defense Sector of Ukraine for Countering Negative Information and Psychological Influence - Heorhii Artiushyn; Sviatoslav Diakov (Pedagogical Discourse, 2025)
The ongoing Russian-Ukrainian war is characterized by the intensive use of the enemy’s information and psychological operations, which have become key instruments influencing the course of military actions and the overall security situation of the state. The development of resilience and analytical competencies plays a crucial role in military training, given the demanding and stressful nature of combat situations.A Program for the Development of Resilience and Analytical Competencies of the Personnel of the Security and Defense Sector of Ukraine for Countering Negative Information and Psychological Influence is proposed. Its main objectives include: forming knowledge about the nature of information and psychological operations and the mechanisms of manipulative influence; developing critical and analytical thinking skills; increasing the level of psychological resilience of service members; acquiring methods of information verification and OSINT-based analysis practices; improving the analytical abilities of military personnel; and training in the implementation of information hygiene procedures and internal information protection. The content of the program combines theoretical knowledge about the mechanisms of information and psychological operations with practical training sessions and simulations aimed at developing the ability to detect manipulative narratives, harmful bot activity, and coordinated information attacks. The program provides for regular training, practical simulations, and crisis-scenario modeling, enabling timely updates of skills in accordance with new tactics and technologies used by the adversary for information and psychological influence.It is concluded that the development of resilience and analytical competencies is a key aspect of military training that enhances the ability of service members to adapt to combat stress and neutralize negative information and psychological influence.